Trypanosoma cruzi trans-Sialidase as a Potential Vaccine Target Against Chagas Disease - da Costa, Kelli Monteiro; Marques da Fonseca, Leonardo; dos Reis, Jhenifer Santos; Santos, Marcos André Rodrigues da Costa; Previato, José Osvaldo; Mendonça-Previato, Lucia; Freire-de-Lima, Leonardo (Frontiers in Cellular and Infection Microbiology, 2021)
Chagas' disease is caused by the protozoan Trypanosoma cruzi, described in the early 20th century by the Brazilian physician Dr. Carlos Chagas. There was a great amount of research devoted to diagnosis, treatment and prevention of the disease. One of the most important discoveries made since then, impacting the understanding of how the parasite interacts with the host’s immune system, was the description of trans-sialidase. It is an unique enzyme, capable of masking the parasite’s presence from the host, while at the same time dampening the activation of CD8+ T cells, the most important components of the immune response. Since the description of Chagas' disease in 1909, extensive research has identified important events in the disease in order to understand the biochemical mechanism that modulates Trypanosoma cruzi-host cell interactions and the ability of the parasite to ensure its survival. The importance of the trans-sialidase enzyme brought life to many studies for the design of diagnostic tests, drugs and vaccines. While many groups have been prolific, such efforts have encountered problems, among them: the fact that while Trypanosoma cruzi have many genes that are unique to the parasite, it relies on multiple copies of them and the difficulty in providing epitopes that result in effective and robust immune responses. In this review, we aim to convey the importance of trans-sialidase as well as to provide a history, including the initial failures and the most promising successes in the chasing of a working vaccine for a disease that is endemic in many tropical countries, including Brazil.